2017
DOI: 10.12688/f1000research.11339.1
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 inhibition for the treatment of pathological organ fibrosis

Abstract: Fibrosis is defined as excess deposition of extracellular matrix, resulting in tissue scarring and organ dysfunction. It is estimated that 45% of deaths in the developed world are due to fibrosis-induced organ failure. Despite the well-accepted role of fibrosis in the pathogenesis of numerous diseases, there are only two US Food and Drug Administration–approved anti-fibrotic therapies, both of which are currently restricted to the treatment of pulmonary fibrosis. Thus, organ fibrosis represents a massive unmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 44 publications
2
44
0
Order By: Relevance
“…JQ1 derivatives are a new class of drugs in cancer therapy now under investigation in human clinical trials (Berthon et al, ; von Schaper, ). Recent studies also have demonstrated that BET inhibitors exhibit profound anti‐fibrotic effects in rodent models of organ failure (Ding et al, ; Duan et al, ; Stratton et al, ). These studies build on the mechanistic rationale that BET inhibitors inhibit the binding of BRD4, which is a nodal, positive regulator of pro‐fibrotic gene expression, and promote extracellular matrix (ECM) deposition and tissue remodeling (Stratton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…JQ1 derivatives are a new class of drugs in cancer therapy now under investigation in human clinical trials (Berthon et al, ; von Schaper, ). Recent studies also have demonstrated that BET inhibitors exhibit profound anti‐fibrotic effects in rodent models of organ failure (Ding et al, ; Duan et al, ; Stratton et al, ). These studies build on the mechanistic rationale that BET inhibitors inhibit the binding of BRD4, which is a nodal, positive regulator of pro‐fibrotic gene expression, and promote extracellular matrix (ECM) deposition and tissue remodeling (Stratton et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a family of epigenetic reader molecules called bromodomain and extraterminal (BET) acetyl-lysine binding proteins was shown to control pathological fibrosis 22 . JQ1, a first-inclass, potent and specific inhibitor of BET bromodomains that functions by competitively displacing BET proteins from acetylated-histones 23 , was found to block cardiac fibrosis in mice subjected to pressure overload or myocardial infarction [24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…The BET family of proteins binds to acetylated chromatin and regulates a series of important biological events . BRD4, a heavily researched BET family member, has been demonstrated to play a key role in the progression of several types of cancer and is considered to be a compelling therapeutic target . The report verified that there was an increased expression of BRD4, indicating a pro‐oncogenic role in Cal27 cells.…”
Section: Introductionmentioning
confidence: 68%